Supernatural and Facebook groups in Indonesia - Wibawa, Aji Prasetya; Aji, Bayu Kuncoro; Filby , Brilliant; Fadhilah, Farhan; Imro’aturrozaniyah, Imro’aturrozaniyah; Istiqlal, Adib (Bulletin of Social Informatics Theory and Application, 2021)
This paper will examine supernatural matters through groups on Facebook using observation methods seen from the group's number of followers, the number of posts, and the things discussed in it to be able to find out how much Indonesian people are interested in supernatural topics. The research phase consists of data collection, pre-processing, processing, and visualization of data. Observations were made by 5 observers by reviewing the group's status (privacy or public), number of members, number of posts per day, and content of the group's content as public. The result of this observation is that the number of members does not promise the activeness of the group when viewed from the number of posts in the group. This is indicated by the number of posts in the immune science group of 4,437,000 with a total of 300 posts and Fortune tellers with 95,271 members with a total of 2260 posts.